Catheter-based intervention for pulmonary vein stenosis due to fibrosing mediastinitis: The Mayo Clinic experience. (1st September 2015) - Ponamgi, Shiva P.; DeSimone, Christopher V.; Lenz, Charles J.; Coylewright, Megan; Asirvatham, Samuel J.; Holmes, David R.; Packer, Douglas L.
Abstract: Introduction: Fibrosing mediastinitis (FM) is a rare but fatal disease characterized by an excessive fibrotic reaction in the mediastinum, which can lead to life-threatening stenosis of the pulmonary veins (PV). Catheter-based intervention is currently the only viable option for therapy. However, the current literature on how best to manage these difficult cases, especially in regards to sequential interventions and their potential complications is very limited. Methods: We searched through a database of all patients who have undergone PV interventions at the Earl H. Wood Cardiac Catheterization Laboratory in Mayo Clinic, Rochester. From this collection, we selected patients that underwent PV intervention to relieve stenosis secondary to FM. Results: Eight patients were identified, with a mean age of 41 years (24–59 years). Five were men, and three were women. Three patients underwent balloon angioplasty alone, and five patients had stents placed. The majority of patients had acute hemodynamic and symptomatic improvement. More than one intervention was required in five patients, four patients had at least one episode of restenosis, and four patients died within four weeks of their first PV intervention. Conclusions: We describe the largest reported case series of catheter-based intervention for PV stenosis in FM. Although catheter-based therapy improved hemodynamics, short-term vascular patency, and patient symptoms, the rate of life-threatening complications, restenosis, and mortality associated with these interventions was found to be high. Despite these associated risks, catheter-based intervention is the only palliative option available to improve quality of life in severely symptomatic patients with PV stenosis and FM. Patients with PV stenosis and FM (especially those with bilateral disease) have an overall poor prognosis in spite of undergoing these interventions due to the progressive and recalcitrant nature of the disease. This underscores the need for further innovative approaches to manage this disease.